Моделювання глибини боридного шару сталі 4Х5МФС при зміні тривалості борування по нанотехнології - Костик, Катерина Олександрівна; Костик, Вікторія Олегівна (My University, 2014)
Отримана модель глибини боридного шару при заданій температурі при зміні тривалості часу борування легованої сталі по нанотехнології, яка спрямована на скорочення тривалості хіміко-термічної обробки при одержанні високоякісних дифузійних шарів, які забезпечують необхідні експлуатаційні властивості виробів. Модель отримана знаходженням рівняння апроксимації з використанням метода найменших квадратів та матричного підходу до регресивного аналізу.

The purpose of the paper was to model boriding layer depth of steel. The temperature was given and time was changed from fifteen to one hundred twenty minutes. Steel 4Cr5МoVSi was research material. A mixture with the content of nanodispersed boroncontaining substances was used in boriding of pastes. This technology reduced the process of chemical-heat treatment. At that, boriding layers obtained high quality and they was providing the necessary performance properties of products. Based on the studies, dependence was obtained of layer depth of boriding time. The model was obtained by the method of approximation with using the method of least squares and matrix approach to regression analysis. Also check was made of the adequacy of the model by the Fisher’s test.
The modeling of boriding layer depth of steel 4CR5МOVSI with changing the time of nanotechnology boriding
Keywords: хіміко-термічна обробка; дифузійний шар; глибина шару; steel; boriding; chemical-heat treatment; diffusion layer; layer depth; model